2019
DOI: 10.1007/s42399-019-00173-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nosocomial Infections and Their Relationships with Demographic Data in Four Different Intensive Care Units of an Education and Research Hospital

Abstract: In all units where health care is provided, especially in intensive care units, infection-related complications are conditions that increase the cost and complicate the treatment process. In our study, in 2014-2015, the Ministry of Health Kartal Dr. Data of 1204 patients followed up in intensive care units of Lutfi Kirdar Training and Research Hospital were analyzed. We excluded the patients with antibiotic therapy at admission to the intensive care unit. Cases followed up in the intensive care unit for less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…The present study also reported a relationship between disease severity and mortality in older adult patients with hospital-acquired infections. This finding is consistent with other studies (38), and hospital-acquired infections put older adult patients at risk of mortality (8). Differences in statistical scores with Apache-II scores could be due to this issue.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study also reported a relationship between disease severity and mortality in older adult patients with hospital-acquired infections. This finding is consistent with other studies (38), and hospital-acquired infections put older adult patients at risk of mortality (8). Differences in statistical scores with Apache-II scores could be due to this issue.…”
Section: Discussionsupporting
confidence: 92%
“…Mortality in the ICU is a multifactorial phenomenon (7). Factors such as type of ICU, reason for hospitalization, age, comorbidities, occurrence of infections, and acute physiological changes during admission and treatment increase patients' mortality prognosis (8,9). The older adults among the high-risk populations are more likely to die in the ICU (8,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation